Project Report Four Station Control and Monitoring By Using Control Area Network(Can Bus) - ASHISH KUMAR DAS,ABHIJIT SHAW,LAKHAN BOGAR,RAJAN PRASAD (2013)
INTERNAL GUIDE : PAVAN H. EXTERNAL GUIDE:KRISHNAMURTHY M. USN NO : 1MJ19EC016,1MJ10EC002,1MJ11EC406,1MJ10EC075. CARRIED OUT AT : M V J College Of Engineering Bangalore-67 ACC N : PR2130
Keywords: Four Station Control and Monitoring By Using Control Area Network(Can Bus)